Overview of the Screen Content Support in VVC: Applications, Coding Tools, and Performance - Nguyen, Tung; Xu, Xiaozhong; Henry, Felix; Liao, Ru-Ling; Golam Sarwer, Mohammed; Karczewicz, Marta; Chao, Yung-Hsuan; Xu, Jizheng; Liu, Shan; Marpe, Detlev; Sullivan, Gary J. (IEEE Transactions on Circuits and Systems for Video Technology, 2021)
In an increasingly connected world, consumer video experiences have diversified away from traditional broadcast video into new applications with increased use of non-camera-captured content such as computer screen desktop recordings or animations created by computer rendering, collectively referred to as screen content. There has also been increased use of graphics and character content that is rendered and mixed or overlaid together with camera-generated content. The emerging Versatile Video Coding (VVC) standard, in its first version, addresses this market change by the specification of low-level coding tools suitable for screen content. This is in contrast to its predecessor, the High Efficiency Video Coding (HEVC) standard, where highly efficient screen content support is only available in extension profiles of its version 4. This paper describes the screen content support and the five main low-level screen content coding tools in VVC: transform skip residual coding (TSRC), block-based differential pulse-code modulation (BDPCM), intra block copy (IBC), adaptive color transform (ACT), and the palette mode. The specification of these coding tools in the first version of VVC enables the VVC reference software implementation (VTM) to achieve average bit-rate savings of about 41% to 61% relative to the HEVC test model (HM) reference software implementation using the Main 10 profile for 4:2:0 screen content test sequences. Compared to the HM using the Screen-Extended Main 10 profile and the same 4:2:0 test sequences, the VTM provides about 19% to 25% bit-rate savings. The same comparison with 4:4:4 test sequences revealed bit-rate savings of about 13% to 27% for Y’CBCR and of about 6% to 14% for R’G’B’ screen content. Relative to the HM without the HEVC version 4 screen content coding extensions, the bit-rate savings for 4:4:4 test sequences are about 33% to 64% for Y’CBCR and 43% to 66% for R’G’B’ screen content.